Evaluation of additives to induce enzymatic activity of Beauveria bassiana conidia and improve insecticidal activity against Diatraea saccharalis (2018)
One important step during the infection process of entomopathogenic fungi is the degradation of the insect cuticle by the secretion of extracellular enzymes such as lipases, proteases and chitinases. Therefore, these enzymes are considered important virulence factors and their expression, excretion and activity have been the objective of diverse studies looking to improve the performance of different biocontrol agents. The aim of this work was to evaluate the conidia-yield and virulence of Beauveria bassiana Bv062 produced with oat-based medium supplemented with potential additives to improve fungal performance